Prototipe e-media pembelajaran zuzo berbasis kue tradisional Palembang - Khalilie, Sabrina; Antari, Luvi; Rizta, Amrina (Papanda Journal of Mathematics and Science Research, 2025)
Mathematics is a subject that is often considered difficult to learn and teach, especially arithmetic operations on integers. This material plays an important role because it is a basic concept that students must master as a foundation for learning subsequent mathematics materials. However, in reality, many students at the junior high school (SMP) level experience difficulties in understanding this material. One of the causes is the use of inappropriate learning media. To overcome this problem, researchers developed an innovation in the form of ZUZO learning e-media that integrates local culture by utilizing traditional Palembang cake as a learning illustration medium. This study aims to determine the level of validity of ZUZO learning e-media based on traditional Palembang cake. The research subjects were 20 respondents from grade VII junior high school students at SMP Muhammadiyah 6 Palembang. The e-media development process refers to the ADDIE (Analysis, Design, Development, Implementation, Evaluation) Development and Research model, but this study was limited to the product development stage. In the analysis stage, researchers conducted direct observations in the field to identify difficulties experienced by students and found that the learning media used was not yet effective. Based on these findings, researchers designed an initial design of learning media that was relevant to students' needs. During the development phase, the ZUZO e-learning media design, based on traditional Palembang cake, was realized using interactive technology. This product was then validated by experts. The validation results showed that the ZUZO e-learning media met the "very valid" criteria. It is suitable for use as a teaching aid for integer arithmetic operations in junior high schools due to its content, appearance, and presentation.